(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
The aim of this research is to present the reality of financial inclusion in Iraq, by analyzing the behavior and trends of its financial indicators according to its dimensions (access and usage) for the period (2014 to 2024). This research aims to determine the level of financial inclusion in Iraq and its most important pillars. Based on the basic premise that financial inclusion in Iraq can be measured and analyzed, and the development of its indicators can be monitored. Financial inclusion in Iraq can be expressed using four sets of indicators: banking density and banking penetration, and the spread of electronic payment services to express access. Mobile payment services, and electronic card and bank account penetration indicators, were used to express usage. Two factors were identified as constraints on achieving financial inclusion requirements in Iraq: the financial infrastructure and technology, and the lack of widespread financial awareness among individuals and the skill required to select financial products. This has led to a lack of digital transaction culture among Iraqis, as well as a lack of confidence in financial transactions in this context, due to the prevalence of hacking, fraud, and deception. It is impossible to advance financial inclusion levels in Iraq without addressing these two important and interconnected constraints.